Spectrophotometric Determination of Valsartan using p-Chloranilic Acid as π-Acceptor in Pure and in Dosage Forms - S. M. Mallegowda,H. N. Deepakumari and H. D. Revanasiddappa (Journal of Applied Pharmaceutical Science, 2013)
The aim of this work was to develop a simple, sensitive and extraction free spectrophotometric method for the quantitative estimation of valsartan in both pure and in pharmaceutical preparations. The developed method is based on the charge transfer complexation reaction between valsartan (VRT) as n- electron donor and p-chloranilic acid (p-CA) as π-acceptor. VRT reacts with p-CA in methanol to produce a bright pink colored complex with a maximum absorption at 530 nm. Beer's law was obeyed in the concentration range of 5-50 µg/mL. The linear regression equation of the calibration graph is A = 0.0081+0.0092C with a regression coefficient (r) of 0.9976 (n = 7). The molar absorptivity is calculated to be 2.06 × 103 L mol-1 cm-1and the Sandell sensitivity is 0.1025 μg cm-2 The limits of detection (LOD) and quantitation (LOQ) values are calculated according to ICH guidelines. The method developed is successfully applied to the determination of VRT in dosage forms.
Keywords: Charge-transfer,spectrophotometry,valsartan,dosage forms.